2010
DOI: 10.1183/09059180.00004110
|View full text |Cite
|
Sign up to set email alerts
|

Isolated splenic metastasis from lung cancer: ringleader of continuous fever

Abstract: The spleen is an infrequent metastatic organ of solid tumours, the prevalence of which ranges between 2.3% and 7.1% in populations with cancer as determined through autopsy. The most common sources of metastasis are breast, lung, colorectal and ovarian carcinoma and melanoma. Isolated metastasis of the spleen is rarely reported with only 93 cases from all sources having been reported up to 2007. Therefore, isolated splenic metastasis from primary lung cancer is exceedingly rare with only 11 cases reported to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
1
23
0
2
Order By: Relevance
“…Therefore, abdominal CT scans should be considered for use if spleen metastasis is suspected. Several studies have reported the clinical significance of FDG-PET/CT scanning in the detection of spleen metastasis from lung cancer (13)(14)(15)(16)(17). In the present case, FDG-PET/CT was useful for confirming the presence of malignant lesions in the spleen.…”
Section: A B Csupporting
confidence: 54%
See 3 more Smart Citations
“…Therefore, abdominal CT scans should be considered for use if spleen metastasis is suspected. Several studies have reported the clinical significance of FDG-PET/CT scanning in the detection of spleen metastasis from lung cancer (13)(14)(15)(16)(17). In the present case, FDG-PET/CT was useful for confirming the presence of malignant lesions in the spleen.…”
Section: A B Csupporting
confidence: 54%
“…The latter two types might not be apparent in abdominal CT scans, although FDG-PET/CT scanning may detect the diffuse type of spleen metastasis. In our previous study, the solitary nodular type was the most common, and in a review of recent case reports, the solitary type was confirmed as the most common type (10,(12)(13)(14)(15)(16)(17)(19)(20)(21)23,26). The differential diagnosis of a solitary nodule or nodules in the spleen includes several diseases, either benign or malignant (31).…”
Section: A B Cmentioning
confidence: 99%
See 2 more Smart Citations
“…This manner of presentation is rare and available literatures are mostly in the form of case reports or descriptive case series containing small number of patients [12,13]. Furthermore, it is extremely difficult to conduct a prospective clinical trial to compare the outcome of chemotherapy vs. metastatectomy in these cases given the rarity of such presentation and existing strong practice preference among various clinicians.…”
Section: Introductionmentioning
confidence: 98%